Factors in the Incidence of Hypertension in the Elderly in Namorih Village - Rani Suraya; Dea Febrina; Faradilla Diwanta; Jelita Suryani Siregar; Junaisa Intan Farashati; Nur Indah Rahma Dilla; Putri Suci Ramadiah; Sheila Megarani; Widya Sabila (PROMOTOR, 2024)
High blood pressure, also known as hypertension, is a medical condition in which blood pressure increases above normal, namely 140/90 mmHg, and carries a risk of morbidity or death (mortality). This disease is often referred to as the silent disease. Irreversible hypertension and modifiable hypertension are two categories of hypertension risk factors. Age, gender, ethnicity and hereditary factors are causes of hypertension that cannot be changed. Smoking, obesity, monotonous lifestyle and stress are modifiable causes of hypertension. In Namorih village, Pancur Batu District, Deli Serdang Regency, North Sumatra, this quantitative research aims to determine the relationship between the incidence of hypertension in older people and the influence of their diet and lifestyle. This type of research is quantitative analytical research with a cross-sectional study research design, which means data is collected simultaneously or all at once. The Namorih Village community produced 60 research samples. Interview results showed that 52 out of 60 adults over 60 years who suffer from hypertension smoke, like salty foods, and rarely exercise. Through education, encouraging a healthy lifestyle, and regular blood pressure checks, it is important to treat hypertension in the elderly. Knowing these risk factors can help prevent and better control hypertension.